The Effect of Using Milking Mechanization on Production at the Rembangan Livestock Breeding and Forage Farms - Wicaksono , Moch. Arif; Widjayanti , Fefi Nurdiana; Fauzi, Nurul Fathiyah (International Applied Science, 2023)
The livestock sub-sector has a strategic role in the development of the agricultural sector, especially in efforts to strengthen food security to meet animal protein needs, strengthen the economic influence of society and accelerate regional development. This research aims to: (1) determine the difference in production before and after milking mechanization, (2) determine the difference in profit levels before and after milking mechanization, (3) determine the break-even point of the dairy business before and after milking mechanization. Determining the research location was carried out purposively (purposive method), namely in Arjasa District, Jember Regency. The method used in this research is descriptive and quantitative methods. for sampling using the total sampling method with a total of 4 respondents. The analyzes used in the research are: (1) production analysis, (2) profit analysis, (3) BEP analysis. The research results show that (1) milk production before mechanization was 3,180 liters/month while milk production after mechanization was 3,394 liters/month, (2) losses before mechanization were IDR. 3,483,101/month, profit after mechanization is IDR. 2,157,605/month, (3) the break-even point (Break Event Point) before mechanization is 3,496 liters and Rp. 38,458,701/month and after mechanization it was 3,214 liters and Rp. 38,569,195/month with an increase of 8.07% and 0.29%.